Electromagnetic Radiations from Heavy Ion Collision - Payal Mohanty; Sabyasachi Ghosh; Sukanya Mitra (Advances in High Energy Physics)
In this review, we have discussed the different sources of photons and dileptons produced in heavy ion collision (HIC). The transverse momentum (pT) spectra of photons for different collision energies are analyzed with a view of extracting the thermal properties of the system formed in HIC. We showed the effect of viscosity on pT spectra of produced thermal photons. The dilepton productions from hot hadrons are considered including the spectral change of light vector mesons in the thermal bath. We have analyzed the pT and invariant mass (M) spectra of dileptons for different collision energies too. As the individual spectra are constrained by certain unambiguous hydrodynamical inputs, so we evaluated the ratio of photon to dilepton spectra, Rem, to overcome those quantities. We argue that the variation of the radial velocity extracted from Rem with M is indicative of a phase transition from the initially produced partons to hadrons. In the calculations of interferometry involving dilepton pairs, it is argued that the nonmonotonic variation of HBT radii with invariant mass of the lepton pairs signals the formation of quark gluon plasma in HIC. Elliptic flow (v2) of dilepton is also studied at sNN=2.76 TeV for 30–40% centrality using the (2+1)d hydrodynamical model.